If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + 3x + -3 = 39 Reorder the terms: -3 + x + 3x + 3x = 39 Combine like terms: x + 3x = 4x -3 + 4x + 3x = 39 Combine like terms: 4x + 3x = 7x -3 + 7x = 39 Solving -3 + 7x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7x = 39 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = 39 + 3 7x = 39 + 3 Combine like terms: 39 + 3 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| X+7x-6x=12 | | 42-2(9+3)=a | | 42-2(9+2)=a | | 8x-2x+5=3x+29 | | (x^2-7x=6)/(x-1)= | | -5x^2+72x+378=502 | | 4x^2+64x=360 | | (3x-1)*(8x+7)= | | x+20x=100 | | d/5-10=10 | | 3w+17=62 | | 35+2e=65 | | h/2-6=10 | | 5-9w=1+3 | | 8x-1/3x | | y+5+3=38 | | 0=-16t^2+vt+0 | | 12w=36 | | e/5+1=2 | | 5e*7e= | | 3x^2+5y^2=7z^2 | | 2y=x+3z+1 | | 5x+3y=2100 | | 8x+2=12x-8 | | x=y-2z | | -18/6-5 | | 7x^2+100=4 | | a+5+2=13 | | x-3x-4=-2x-3-1 | | sqrt(14-(-35)-10)= | | 5(2x-9)+11=12x-2(x+18)+1 | | y=2x^2+3x+0 |